‘Fear, good servants, bad lords’: fear of the other in Ursula K. Le Guin’s the left hand of darkness - Suzana Haji Muhammad; Sujuan Li (Cogent Arts & Humanities)
Ursula K. Le Guin’s renowned novel The Left Hand of Darkness offers a profound exploration of the multifaceted fears of the other through its futuristic setting and imaginative narrative. Building on Simon C. Estok’s argument that various forms of fear like misogyny, racism, homophobia, xenophobia and ecophobia are inherently linked, originating from ‘maladaptive, reflexive, and somewhat unconscious condition that is based in affect’, this study delved into Genly Ai’s struggle with misogyny and homophobia, the fear exhibited by Orgoreyn politicians towards other individuals, and the xenophobia portrayed by characters such as Argarven and Tibe, the Terrans’ ecophobia. This academic exploration aimed to unravel strategies for confronting the fear of the other in constructive ways. By employing a thematic analysis of the fiction, the study advocated for the adoption of a ‘leap of faith’ as a means to foster harmonious relationship with the human other, whether at the level of the individual or the community. Additionally, the study emphasized the importance of cultivating reverence for nonhuman nature as a pivotal component in alleviating ecophobia. The study acknowledged the importance to transform the fear of the other from a divisive force into a bridge for communication and compassion, discouraging its use as a source of conquest and animosity.